PHANGS-HST Catalogs for ∼100,000 Star Clusters and Compact Associations in 38 Galaxies. II. Physical Properties from Decision-tree-based Spectral Energy Distribution Fitting of NUV-U-B-V-I Photometry with Categorical Priors Set by Hα Emission, Cluster Morphology, and Other Auxiliary Information - David A. Thilker; Janice C. Lee; Bradley C. Whitmore; Daniel Maschmann; Kiana Henny; Rupali Chandar; Daniel A. Dale; Sinan Deger; Médéric Boquien; Aida Wofford; Leonardo Úbeda; Alessandro Razza; et al. (The Astrophysical Journal Supplement Series)
This paper is the second in a series presenting the catalogs and properties of the largest sample to date of ∼100,000 star clusters and compact associations, in 38 spiral galaxies observed by the PHANGS-HST Treasury survey. Here, we present spectral energy distribution (SED) fitting techniques used to compute the age, mass, and reddening for each object. Our decision-tree-based strategy incorporates categorical priors on model age, reddening, and metallicity determined from additional observed parameters: localized H α emission, source morphology, and demographic-specific locations in the UBVI color–color diagram. This approach is implemented to mitigate model degeneracies, particularly between young dusty clusters and old clusters with minimal dust, which can have identical optical colors. Results based on H α narrowband imaging from the ground and from Hubble Space Telescope are intercompared, and contrasted with previous SED-fitting efforts. The fraction of the population that is subject to such priors is ∼14%, and of this subset, ∼63% of old globular clusters (GCs) have ages that change by a factor of 10 or more relative to unconstrained fits with single metallicity ( Z _⊙ ) simple stellar population models. The demographics of the population are examined through age–mass and age–reddening diagrams (for individual galaxies as well as aggregated over the sample), and the GC mass function. We demonstrate relationships between cluster age–mass diagrams and properties of parent galaxies (galaxy morphology and location relative to the galaxy main sequence). We outline continuing efforts to improve the inference of physical properties, including the incorporation of JWST infrared photometry and updated synthesis models.